Fenomenologi penerapan 3M (Mencuci tangan, Memakai masker dan Menjaga jarak) santri di Pondok Pesantren Darul ‘Ulum Jombang - Ningtyas, Ferra Widya; Yani, Athi Linda; Mukarromah, Indah (Universitas Muhammadiyah Magelang, 2022)
WHO has officially declared COVID-19 a global pandemic. Islamic boarding schools are one of the arrangements that need to be implemented to prevent the spread of Covid-19. There are 9,369 students at the Darul 'Ulum Jombang Islamic Boarding School that have the potential to spread Covid-19 infections. Efforts to prevent the spread of Covid-19 were carried out by implementing 3M in accordance with the appeal of the government task force. The purpose of the study was to find out the phenomenon of the application of 3M (Washing hands, wearing masks and maintaining distance) of students at the Darul 'Ulum Islamic Boarding School Jombang. The research design used is qualitative research with descriptive phenomenological methods. The social situation is all students of the XV Al-Falah dormitory and the IV I Ainusyams dormitory. The participants were 6 students using purposive sampling technique. researchers as an instrument using interview guidelines, data collection using in-depth interview techniques. Data analysis using the Colaizzi method. The results of the study obtained 5 themes 1) Knowledge level 2) Breaking the rules 3) Confidence 4) Support from hostel caregivers and 5) Obeying the rules. Santri can implement 3M because they have knowledge, there is support from hostel caregivers who provide facilities and infrastructure, strict regulations and supervision make students have self-awareness. The reason students don't do 3M is because they are influenced by friends, the belief that not doing 3M makes them sick and the belief that doing 3M or not can make you sick if God wills.